Inflammatory fibroid polyp in ileum causing adult intussusceptions - Kafle, Santosh Upadhyay; Upadhyaya, P; Karki, S; Adhikary, S; Agarwal, R (Health Renaissance, 2013)
Inflammatory fibroid polyps are believed to occur in response to local noxious stimuli. They are uncommon benign but well documented solitary polypoid lesions occurring in gastrointestinal tract; most commonly in stomach. A rare entities of two adult intussusceptions due to inflammatory fibroid polyp in ileum has been reported in this article. Health Renaissance, January-April 2013; Vol. 11 No.1; 166-168 DOI: http://dx.doi.org/10.3126/hren.v11i2.8227